Music in the education of students with special needs education in Spain: Legislative analysis and proposal for improvement - Sabbatella, Patricia L.; del Barrio Aranda, Luis (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2021)
This article presents an analysis of the musical situation in the education of students with special educational needs enrolled at Pre-school, Primary and Special Education levels. Based on a documentary review of the legislation that regulates the Spanish Educational System from the General Education Law (LGE, 1970) to the Organic Law 3/2020, which amends the Organic Law on Education (LOMLOE, 2020), implications of music in the education of students with special educational needs, its educational function, the music teacher’s profile and suggestions for improvement are presented.